Aplicación de la metodología Design Thinking para el mejoramiento del proceso de Titulación de la Carrera de Ingeniería Industrial de la Universidad Técnica de Cotopaxi. - Fonseca Gualotuña, Dayana Elizabeth (2021)
It has been identified that the Industrial Engineering Major has a graduation rate of less than 20% due to different academic, administrative and human factors. The improvement of this indicator is a concern of the authorities of the Major and the Faculty of Engineering and Applied Sciences (CIYA). In addition, transition of M4 curriculum from ten to eight academic cycles requires the approval of a new Graduation By-law. For this reason, the stages proposed by the Design Thinking (DT) methodology have been applied in this project. First of all, it has been empathized with the whole actors involved in the current graduation process, like students, graduates, teachers, administrative personnel and authorities in order to identify all the problems that arise during the process. Due to the fact that the Graduation Unit process did not exist, this activity was also performed. Then the most important drawbacks were defined using Pareto charts. In the third stage of the DT, recommendations were ideated in order to academic authorities of the Faculty and the University take into account when preparing the new regulations. The application of the recommendations collected in this research study will benefit students, teachers and all areas related to the process, so that the development of the degree work and interaction between all people involved is more effective and, in this way, improve the graduation rate of the Industrial Engineering Major, complying with quality and excellence standards.